2017
DOI: 10.1002/phar.1918
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Patients Treated with IV Beta‐Lactam/Beta‐Lactamase Inhibitor Combinations

Abstract: Study Objective Increased acute kidney injury (AKI) incidence has been reported in patients receiving piperacillin-tazobactam (PTZ) therapy compared to other beta-lactams. This study sought to determine if the addition of beta-lactamase inhibitors impact AKI incidence by comparing patients treated with PTZ or ampicillin-sulbactam (SAM). Design Retrospective cohort study Setting Large academic tertiary care hospital Patients Overall, 2,448 patients received PTZ (n=1,836) or SAM (n=612) for at least 48 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“… 12–16 There are no studies comparing piperacillin and piperacillin/tazobactam with regard to nephrotoxicity. A matched-cohort study performed by Rutter and Burgess, 32 in which patients were stratified according to vancomycin exposure, compared piperacillin/tazobactam with ampicillin/sulbactam with regard to renal function. Results showed that the likelihood of AKI increased with the addition of vancomycin to piperacillin/tazobactam compared with piperacillin/tazobactam alone, but not when vancomycin was added to ampicillin/sulbactam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12–16 There are no studies comparing piperacillin and piperacillin/tazobactam with regard to nephrotoxicity. A matched-cohort study performed by Rutter and Burgess, 32 in which patients were stratified according to vancomycin exposure, compared piperacillin/tazobactam with ampicillin/sulbactam with regard to renal function. Results showed that the likelihood of AKI increased with the addition of vancomycin to piperacillin/tazobactam compared with piperacillin/tazobactam alone, but not when vancomycin was added to ampicillin/sulbactam.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that the addition of a β-lactamase inhibitor is not responsible for the increased rates of AKI observed in patients treated with piperacillin/tazobactam + vancomycin. 32 Another hypothesis suggests that the concomitant occurrence of interstitial nephritis (caused by piperacillin/tazobactam) and oxidative stress (caused by vancomycin) may lead to a stronger decline in renal function compared with monotherapy. However, a recent experimental study using a rat model showed no additional histopathological kidney injury with combination therapy when compared with monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that baseline renal function or pre-existing renal disease is not associated with higher risk of AKI when treated with VPT as opposed to vancomycin alone. Renal impairment has not been shown to be predictive of VPT nephrotoxicity [14,15,[51][52][53][54] nor in other dual antimicrobial combinations with vancomycin [54]. In small studies, the limited numbers of patients with renal impairment precluded analysis for association with AKI [13].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…The mechanisms for the increased rates of nephrotoxicity with piperacillin-tazobactam have been unclear. Data suggest that the association is not due to the beta-lactamase inhibitor or the infusion strategy [32]. Some have even suggested that the increase in serum creatinine with piperacillin-tazobactam does not represent nephrotoxicity in these patients.…”
Section: Patient Assessmentmentioning
confidence: 99%